2017
DOI: 10.1209/0295-5075/118/50001
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally freezing quantum discord in a dephasing environment using dynamical decoupling

Abstract: The discovery of the intriguing phenomenon that certain kinds of quantum correlations remain impervious to noise up to a specific point in time and then suddenly decay, has generated immense recent interest. We exploit dynamical decoupling sequences to prolong the persistence of timeinvariant quantum discord in a system of two NMR qubits decohering in independent dephasing environments. We experimentally prepare two-qubit Bell-diagonal quantum states that interact with individual dephasing channels and demonst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…[71] an experimental algorithm allowing the tomographic reconstruction of the density matrix of a two-qubit system has been proposed as basis to evaluate quantum discord. It is worth noticing how the diagonal Bell states, studied in this paper, play a prominent role for such kind of investigations thanks to their properties and their robustness exhibited also in open quantum systems immersed in dephasing environment [72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…[71] an experimental algorithm allowing the tomographic reconstruction of the density matrix of a two-qubit system has been proposed as basis to evaluate quantum discord. It is worth noticing how the diagonal Bell states, studied in this paper, play a prominent role for such kind of investigations thanks to their properties and their robustness exhibited also in open quantum systems immersed in dephasing environment [72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Cianciaruso et al [649] demonstrated the freezing phenomenon of Bures distance-based GQD for a specific class of BD states, each party of which is independently interacting with a non-dissipative decohering environment. The conditions for choosing a set of initial states to freeze QD, have also been investigated for other environmental conditions [650][651][652].…”
Section: A Freezing Of Quantum Discordmentioning
confidence: 99%
“…Furthermore, in the literature, some schemes are used to enhance the time-interval in which quantum correlations remain constant and control the appearance of sudden transition time e.g. dynamical decoupled method and non-Markovianity [24][25][26]. Unfortunately, these controlled schemes have some restrictions, for example, in the short-time interactions, the dynamical decoupling is an inappropriate technique because of the lack of memory issue [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…We show for the first time that the phenomena of freezing and sudden transition still occurs even when the quantum system interacts with a nonequilibrium environment in both weak and strong coupling regimes for certain Bell diagonal states. Interestingly, unlike the application of two-flip dynamical decoupling pulse sequence technique [24][25][26], here the time interval in which the quantum correlation is unaffected by the decoherence can be further extended only by allowing the environment to deviate from equilibrium. This reflects that the non-equilibrium feature offers an efficient alternative protocol to delay the occurrence of the sudden transition time and combat against the environmental noise.…”
Section: Introductionmentioning
confidence: 99%